2007
DOI: 10.1021/jp065695q
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of 19F and 29Si NMR Shifts and Stabilities of F- Encapsulating Silsesquioxanes

Abstract: Hartree-Fock and density functional theory techniques have been used to calculate the structures, the stabilities in aqueous and toluene solutions, and the 19 F and 29 Si NMR shifts of Fencapsulating double-ring geometry silsesquixoanes DnR with n ) 3-6. We find for the fluorides that the encapsulation free energy is most negative for the double four-ring (D4R) cage, in which the most stable geometry has Fin the center. For n ) 5, 6 (and for an opened version of the double five-ring, D5R, cage), the most stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…This is also different with the fact that the F − is encapsulated in the center of the silicon analogue, T 8 [9]. Nevertheless, Tossell has found that in the larger POSS such as T 10 and T 12 with the double-decker structure F − is bound at the Si atom in a corner of the cage so the present result resembles that [12].…”
Section: Insertion Of Anions Of Halogen Elements (F − and CL − )contrasting
confidence: 73%
See 3 more Smart Citations
“…This is also different with the fact that the F − is encapsulated in the center of the silicon analogue, T 8 [9]. Nevertheless, Tossell has found that in the larger POSS such as T 10 and T 12 with the double-decker structure F − is bound at the Si atom in a corner of the cage so the present result resembles that [12].…”
Section: Insertion Of Anions Of Halogen Elements (F − and CL − )contrasting
confidence: 73%
“…The structures of the complexes and reaction paths of the halogen anions investigated here (especially F − ) are significantly different with those of the rare gas or cationic elements in the preceding sections. Incidentally, there are many comprehensive studies for the encapsulation of F − into POSS, and it is well known that the endohedral complex F − @T 8 has been observed experimentally [7,8,12].…”
Section: Insertion Of Anions Of Halogen Elements (F − and CL − )mentioning
confidence: 99%
See 2 more Smart Citations
“…Alkali metals from Na + to Cs + stabilized different oligomers, with Li + -H 2 O interactions further enhan-cing polymerization in the case of Li + . Tossell 20 has explained the role of fluoride ion F À in promoting the formation of D4R cubes. A comparative study of substituted ammonium, NA 4 + , shows markedly different results depending on whether the alkyl group A is methyl, ethyl, or propyl.…”
Section: Generation and Perpetuation Of Remedy-specific Silicatesmentioning
confidence: 99%